2017
DOI: 10.1155/2017/4109208
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of the Standard Cross-linking Outcomes in Adult Keratoconus: One-Year Follow-Up

Abstract: Purpose To evaluate the effects of preoperative presumed predictor factors on clinical and topographic outcomes in adult keratoconus (KC) 1 year after the standard corneal cross-linking (CXL). Design Retrospective cohort study. Methods The study included 84 KC patients (136 eyes) who were treated with conventional CXL. Postoperative best-corrected visual acuity (BCVA) and K max were considered the main predicted variables. The entire participants were divided into subgroups with cutoff values in accordance wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(38 reference statements)
3
13
0
Order By: Relevance
“…However, patients in whom CXL failed had a thinner cornea (p < 0.01 * ) when failure was defined as the presence of one or both criteria. Studies in the literature contradict one another concerning pachymetry; findings of Godefrooij et al are comparable with ours [21], Badawi et alshowed in their study that thinner corneas were good predictors for postoperative CDVA improvement only without any effect on keratometry [18] while Toprak et al stated that thinner corneas exhibited more flattening post-CXL [26].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, patients in whom CXL failed had a thinner cornea (p < 0.01 * ) when failure was defined as the presence of one or both criteria. Studies in the literature contradict one another concerning pachymetry; findings of Godefrooij et al are comparable with ours [21], Badawi et alshowed in their study that thinner corneas were good predictors for postoperative CDVA improvement only without any effect on keratometry [18] while Toprak et al stated that thinner corneas exhibited more flattening post-CXL [26].…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, the mean TP showed a significant reduction than the baseline values (p < 0.01 * ). Other studies reported the same results, suggesting that the postoperative thinning may be due to compression of collagen fibrils, changes in corneal hydration and edema, and keratocyte apoptosis [15,18,19]. On the contrary, corneal thickness remained unchanged in other series [11].…”
Section: Discussionmentioning
confidence: 54%
“…The two most significant indicators of improvement in vision after corneal CXL were the preoperative values of low CDVA (≤ 20/40) and high K-max values (≥ 55 D). 1 , 8 , 20 , 21 In the current study, the central KCs exhibited lower average values for the preoperative CDVA, with higher K-max values (0.25 ± 0.04 log MAR and 56.6 D) compared to paracentral KC (0.1 ± 0.2 log MAR and 53.84 D), which could explain these results. The greater improvement in the CDVA in the central cones is in accordance with what has been published by other authors, 22 , 23 and this may be due to the fact that the central area is closer to the radiation of the CXL, so the intensity of radiation is higher than in the paracentral region, plus the depth does not appear to be homogeneous within the treatment area, exhibiting a decrease towards the periphery of the cornea.…”
Section: Discussionsupporting
confidence: 41%
“…Some authors have reported significant improvement of BCDVA [ 15 , 40 , 41 ], while others did not support that [ 12 , 14 , 31 ]. According to some recently available data [ 42 44 ], preoperative keratometry has a significant impact on postoperative outcome in terms of visual acuity, i.e. patients with higher preoperative keratometry values are likely to show more improvement in BCDVA.…”
Section: Discussionmentioning
confidence: 99%